What Do New Zealanders Think About Freshwater Fish? Results From a National Survey - Marc Tadaki; Alaric McCarthy; Fabio Weiss; Aisling Rayne; Sarah Crowley; Alexis Farr; Leah Gibbs; Jane Kitson; Nick Reo; Philip Stahlmann‐Brown (New Zealand Journal of Marine and Freshwater Research, 2026)
The 2025 Environmental Perceptions Survey provides unique insight into a nationally representative sample ( n = 1024) of New Zealanders’ perceptions of freshwater fish. About 8% of the sample had fished in the past 12 months and 30% had fished ever, and fisher subsamples were more male, more Māori and younger than the New Zealand population. Perceived awareness of local freshwater fish presence was higher for fishers than non‐fishers for all species, but both shared highest awareness of eel/tuna, whitebait and trout, which are also the most commonly fished species. Assessment of national fishing popularity and fishing pressure was mixed, but regional trends are evident. Respondents agreed that there are not enough freshwater fish, that fishers should be able to eat what they catch and that fish are healthy enough to eat. Respondents prefer more of all freshwater fish species rather than only one or two species. This data can help understand how people's relationships with freshwater and fish are changing and possibilities for building alliances for freshwater stewardship.

Leveraging long-term monitoring data to examine the restorative effects of aquaculture - Al Alder; Leigh Michael Howarth; Fabio Weiss; Javier Atalah (Aquaculture, 2026)